Breakfast consumption-related perceived behaviour control and subjective norms among girl adolescents: Applying an indirect measurement - Nasrin Shirvani; Mohtasham Ghaffari; Sakineh Rakhshanderou (Wolters Kluwer Medknow Publications, 2021)
BACKGROUND: Healthy nutrition in childhood and adolescence is important for growth and development. Breakfast is the most important meal during a day, and many studies have linked eating breakfast to good health. The aim of the present study was to evaluate the subjective norms and perceived behavioural control of Iranian teenage girls about breakfast consumption and its related factors in 2018. MATERIALS AND METHODS: In this descriptive-analytical study, 320 female students were enrolled using a multistage sampling method. Data were collected using a questionnaire, the validity and reliability of which were evaluated. Data analysis was carried out using SPSS16 software and ANOVA and t independent tests. RESULTS: There was a significant relationship between students' sleep duration and the people with whom they eat breakfast with the Motivation to Comply (P = 0.009), (P = 0.001) and subjective norms (P = 0.004), (P = 0.001) as well as between the people with whom they eat breakfast and normative beliefs (P = 0.05). There was a significant relationship between father's job and control beliefs (P = 0.03) and perceived behavioural control (P = 0.04), between household size with perceived behavioural control (P = 0.05), between sleep duration and perceived power (P < 0.001), and perceived behavioural control (P = 0.03), between the people with whom they eat breakfast with control beliefs (P < 0.001), perceived power (P < 0.001), and perceived behavioural control (P < 0.001). CONCLUSION: Considering the importance of sleep duration for adolescent girls as well as eating breakfast with other family members, health policymakers are recommended to pay special attention to these two factors while designing educational interventions.